Regional Planning for the Extraction of Non-energy Raw Materials: an analysis of requirements, Problems and options on the Basis of experiences in north rhine-Westphalia - von Seht, Hauke (Raumforschung und Raumordnung | Spatial Research and Planning, 2010)
Controlling the extraction of non-energetic mineral resources is not only a highly complex and spatially important task in planning. It is also a politically and legally increasingly challenged task. This article calls for regional planning authorities to take on this challenge and to set up concentration zones for surface mining. Furthermore, it is examined, which special circumstances and grave difficulties this planning task involves and how these difficulties can be overcome.